1999
DOI: 10.1088/0268-1242/14/5/006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alloy potential fluctuations in InGaN epitaxial films

Abstract: Results of photoluminescence and photoconductivity measurements in In x Ga 1−x N epitaxial films are presented. The photoluminescence peak energy and intensity show several anomalous behaviours. The peak energy changes with temperature exhibiting an inverted S-shape dependence, where it decreases, then increases with increasing temperature in the range 40-100 K and finally decreases with increasing temperature. The intensity shows a temperature dependence similar to that of amorphous semiconductors and disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 29 publications
4
39
0
Order By: Relevance
“…The photoionization of such a state proceeds in two steps resulting in the non-exponential kinetics of photoconductivity growth [2][3][4][5][6][7][8]. In consequence, the kinetics are modelled with formula…”
Section: Introductionmentioning
confidence: 99%
“…The photoionization of such a state proceeds in two steps resulting in the non-exponential kinetics of photoconductivity growth [2][3][4][5][6][7][8]. In consequence, the kinetics are modelled with formula…”
Section: Introductionmentioning
confidence: 99%
“…The increase of In content clearly shows the aggravation of the S-shaped behavior of PL peak energy. According to Lin et al [5], the recombination of electron-hole (e-h) pair is considered to occurs around the localized states. The e-h recombination pair increases with In content in In x Ga 1Àx N epilayers due to strong alloy potential fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, room temperature photoluminescence (PL) emission from Si-doped In x Ga 1Àx N epilayers was found to be much stronger than that of undoped In x Ga 1Àx N epilayers. The influence of doping on the optical and structural characteristics of In x Ga 1Àx N/GaN heterostructures (HS) and In x Ga 1Àx N/GaN multi-quantum wells (MQWs) has been examined by many researchers using optical absorption (OA), PL, photoluminescence excitation (PLE) and X-ray diffraction (XRD) measurements [4,5]. In In x Ga 1Àx N/GaN MQWs, the effects of Si doping in the GaN barriers have been reported [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This is most likely caused by the alloy fluctuation in these samples. Previous studies [14] of PL lifetime have shown that the stretched exponential decay model [15,16] can offer insight into the recombination mechanisms in InGaN-related structures. According to this model the PL intensity decay is described by the following expression:…”
Section: Resultsmentioning
confidence: 99%